1996
DOI: 10.1007/bf00311502
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of d(?)3-hydroxybutyrate administered to rats with extensive burns

Abstract: Although the suppressive effect of 3-hydroxybutyrate (3-OHB) on post-traumatic protein catabolism in traumatized patients is well documented, the oxidation of exogenously administered 3-OHB during catabolic stress has not been investigated. The present study was designed to evaluate, using radioactive isotopes, total body oxidation in rats with and without burn stress to which 3-OHB had been exogenously administered, in comparison with total body oxidation in such rats that had received glucose. The rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We have administered 3-hydroxybutyrate after trauma,4 hemorrhage,5,12 and extensive burns. 13 We have confirmed that ketone bodies are well oxidized and have metabolic effects, such as suppression of hyperglycemia and proteolysis, after these injuries.13 For not only severely traumatized patients but also patients undergoing elective surgery, ketone bodies may have more general use as nutrition support.…”
Section: Discussionmentioning
confidence: 55%
“…We have administered 3-hydroxybutyrate after trauma,4 hemorrhage,5,12 and extensive burns. 13 We have confirmed that ketone bodies are well oxidized and have metabolic effects, such as suppression of hyperglycemia and proteolysis, after these injuries.13 For not only severely traumatized patients but also patients undergoing elective surgery, ketone bodies may have more general use as nutrition support.…”
Section: Discussionmentioning
confidence: 55%